The Determination of Inpatient Room Unit Cost Using ABC Method at PKU Muhammadiyah Nanggulan Hospital-Yogyakarta - Hafni, Diska Arliena (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study analyses the determination of the unit cost of inpatient room rates at PKU Muhammadiyah Nanggulan, Kripulonprogo-Yogyakarta by using the Activity-Based Costing (ABC) method. This research is quantitative research. The research data were obtained through interviews, documentation, and observation. Then, the data were analysed using a comparative descriptive analysis method with a quantitative approach. The results of the study showed that the determination of unit costs using the ABC system was higher than the traditional methods used by the hospital.